The impact of digital marketing and entrepreneurial munificence on rural business performance - Mohamad, Mohd Amin (Zes Rokman Resources, 2024)
The objectives of this research are twofold. Firstly, to examine the effects entrepreneurial munificence on the business performance of small rural businesses in Malaysia. Secondly, this research also investigates the effects of the online business platform which is also called digital marketing platform on the rural small business performance. There is a gap related to research related to the impact of COVID-19 pandemic which are focusing those in the cities. However, less research has been done to those in the rural areas. This research is using the quantitative methodology to collect and analyze data. Questionnaire instruments are used as the tool to collect data from the rural small business owners. Completed survey data was collected from 133 respondents from various locations in Melaka was analyzed using IBM SPSS.